Genomic Characterization of Leishmania tropica in Cutaneous Leishmaniasis, Somali Region, Ethiopia, 2023 - Adugna Abera; Pieter Monsieurs; Myrthe Pareyn; Dereje Beyene; Geremew Tasew; Allison Aroni-Soto; Mahlet Belachew; Desalegn Geleta; Bethlehem Adnew; Bokretsion Gidey; Henok Tadesse; Atsbeha Gebreegziabxier; et al. (Emerging Infectious Diseases)
We sequenced Leishmania tropica genomes from 8 human skin samples collected in a newly emerging focus of cutaneous leishmaniasis in the Somali region of Ethiopia. We found a variant with unique genomic signatures of drug resistance. Public health officials should use genomic surveillance to slow expansion of L. tropica.